Arabidopsis NahG Plants as a Suitable and Efficient System for Transient Expression using Agrobacterium tumefaciens - Rosas-Díaz, Tábata Victoria; Cana Quijada, José Francisco; Amorim-Silva, Vitor; Botella-Mesa, Miguel Ángel; Lozano Durán, Rosa; Bejarano, Eduardo R. (Science direct, 2017)
aken together, our results show that expression of the NahG transgene in Arabidopsis dramatically enhances the efficiency of Agrobacterium-mediated transformation in rosette leaves, enabling the routine use of this technique in transient assays. This method can be successfully applied in SA-depleted Arabidopsis plants for transient expression-based functional assays routinely done in N. benthamiana, which would facilitate the use of the plethora of tools and knowledge generated in Arabidopsis. The use of this assay does not require complex inoculation media, supplements, or specific growth conditions, and can be used with different Agrobacterium strains. A high level of expression has also been previously achieved in Arabidopsis transgenic plants containing an inducible cassette to express the bacterial effector AvrPto from a DEX-inducible promoter (Tsuda et al., 2012). However, the assay reported here overcomes the use of DEX treatment and the putative multi-side effects potentially derived from the expression of a bacterial effector that interferes with multiple receptor-like kinases and whose constitutive expression is most likely detrimental for the plant.
Keywords: Plantas - Investigación; NahG; Transient Expression; Arabidopsis